A prospective study of risk factors associated with seroprevalence of SARS-CoV-2 antibodies in healthcare workers at a large UK teaching hospital. Issue 5 (November 2022) - Cooper, Daniel J; Lear, Sara; Watson, Laura; Shaw, Ashley; Ferris, Mark; Doffinger, Rainer; Bousfield, Rachel; Sharrocks, Katherine; Weekes, Michael P.; Warne, Ben; Sparkes, Dominic; Jones, Nick K; et al.
Highlights: The risk of SARS-CoV-2 infection in healthcare workers is highly heterogeneous The risk of SARS-CoV-2 is significantly higher in BAME healthcare workers Working in COVID-19 specific areas increases the risk of infection Porters, domestic staff, and healthcare assistants are healthcare staff at highest risk of SARS-CoV-2 infection. Abstract: Objectives: To describe the risk factors for SARS-CoV-2 infection in UK healthcare workers (HCWs). Methods: We conducted a prospective sero-epidemiological study of HCWs at a major UK teaching hospital using a SARS-CoV-2 immunoassay. Risk factors for seropositivity were analysed using multivariate logistic regression. Results: 410/5, 698 (7·2%) staff tested positive for SARS-CoV-2 antibodies. Seroprevalence was higher in those working in designated COVID-19 areas compared with other areas (9·47% versus 6·16%) Healthcare assistants (aOR 2·06 [95%CI 1·14-3·71]; p =0·016) and domestic and portering staff (aOR 3·45 [95% CI 1·07-11·42]; p =0·039) had significantly higher seroprevalence than other staff groups after adjusting for age, sex, ethnicity and COVID-19 working location. Staff working in acute medicine and medical sub-specialities were also at higher risk (aOR 2·07 [95% CI 1·31-3·25]; p <0·002). Staff from Black, Asian and minority ethnic (BAME) backgrounds had an aOR of 1·65 (95% CI 1·32 – 2·07; p <0·001) compared to white staff; this increased risk was independent of COVID-19 area working. The only symptoms significantly associated with seropositivity in a multivariable model were loss of sense of taste or smell, fever, and myalgia; 31% of staff testing positive reported no prior symptoms. Conclusions: Risk of SARS-CoV-2 infection amongst HCWs is highly heterogeneous and influenced by COVID-19 working location, role, age and ethnicity. Increased risk amongst BAME staff cannot be accounted for solely by occupational factors.